Emerging Role of Extracorporeal Support in Acute and Acute-on-Chronic Liver Failure: Recent Developments - MacDonald, Andrew J.; Karvellas, Constantine J. (Seminars in Respiratory and Critical Care Medicine, 2018)
Acute liver failure (ALF) and acute-on-chronic liver failure (ACLF) are life-threatening illnesses requiring intensive care admission and potentially liver transplantation. Artificial extracorporeal liver support (ECLS) systems remove water-soluble and albumin-bound toxins to maintain normal serum chemistry, prevent further hepatic/organ system damage, and create an environment for potential hepatic regeneration/recovery (ALF) or bridge to liver transplantation (ALF and ACLF). Use of artificial ECLS has been studied in both ALF and ACLF. Artificial ECLS systems have been found to be safe and have demonstrated the following benefits: improvement of biochemistries, hemodynamic status, and hepatic encephalopathy. Despite this, only one prospective randomized controlled trial examining the use of high-volume plasma exchange has demonstrated improvement in transplant-free survival. Bioartificial (cell-based) ECLS systems build on the technology of artificial systems, incorporating living hepatocytes in a bioactive platform to further mimic endogenous hepatic detoxification and synthetic functions. Currently, no bioartificial system has been found to confer a mortality benefit; however, these platforms offer the greatest potential for future development.
Keywords: extracorporeal liver support; albumin dialysis; acute liver failure; acute-on-chronic liver failure; extracorporeal liver-assist device; liver transplantation